Enhancing predicted fluoride varnish efficacy and post-treatment compliance by means of calcium-containing gummy bears. (June 2018) - Lippert, F.; Al Dehailan, L.; Castiblanco, G.A.; Tagelsir, A.A.; Buckley, C.; Eckert, G.J.
Abstract: Objectives: This study determined whether consumption of calcium-containing gummies prior to fluoride varnish application enhances plaque fluoride retention and compliance with post-varnish application instructions. Methods: The present study followed a multi-center, parallel, randomized, and laboratory analyst-blind design. Following IRB approval, parent consent and child assent, 44 subjects (7–12 years), were randomized to either gummy or no-gummy study groups. A baseline plaque sample was obtained after a wash-out period. Fluoride varnish (5% NaF) was applied; subjects in the gummy group received two calcium-containing gummies prior to varnish application. Subjects were given two questionnaires to complete (subject and parent) to investigate adherence to post-treatment instructions. Three days later, a second plaque sample was obtained. Plaque was analyzed for plaque fluid and solid fluoride concentrations. Fluoride data were analyzed using Wilcoxon Rank Sum tests, questionnaire data using Pearson chi-square tests. Results: Plaque fluid fluoride did not change pre- to post-treatment in the gummy group (mean ± sd: 8.8 ± 5.7 μmol/l vs. 10.0 ± 6.3 μmol/l; p = 0.265) or in the no-gummy group (8.1 ± 4.4 μmol/l vs. 16.1 ± 20.0 μmol/l; p = 0.058). Groups were not different for plaque fluid fluoride pre-treatment (p = 1.000), post-treatment (p = 0.904), or change (p = 0.904). Plaque solid fluoride did not change pre- to post-treatment in the gummy group (0.89 ± 1.10 μmol/g vs. 1.37 ± 1.77 μmol/g; p = 0.073) or in the no-gummy group (0.68 ± 0.77 μmol/g vs. 2.01 ± 5.00 μmol/g; p = 0.190). Groups were not different for plaque solid fluoride pre-treatment (p = 1.000), post-treatment (p = 0.466), or change (p = 0.874). No significant differences were found between groups for questionnaire responses. Conclusion: This study failed to demonstrate an effect of calcium-containing gummies in enhancing plaque fluoride retention. Clinical significance: The consumption of calcium-containing gummies prior to fluoride varnish application does not promote greater intra-oral fluoride retention or better adherence to post-treatment instructions.